An Opinion Paper on Aerogels for Biomedical and Environmental Applications - Carlos A. García-González; Tatiana Budtova; Luisa Durães; Can Erkey; Pasquale Del Gaudio; Pavel Gurikov; Matthias Koebel; Falk Liebner; Monica Neagu; Irina Smirnova (Molecules, 2019)
Aerogels are a special class of nanostructured materials with very high porosity and tunable physicochemical properties. Although a few types of aerogels have already reached the market in construction materials, textiles and aerospace engineering, the full potential of aerogels is still to be assessed for other technology sectors. Based on current efforts to address the material supply chain by a circular economy approach and longevity as well as quality of life with biotechnological methods, environmental and life science applications are two emerging market opportunities where the use of aerogels needs to be further explored and evaluated in a multidisciplinary approach. In this opinion paper, the relevance of the topic is put into context and the corresponding current research efforts on aerogel technology are outlined. Furthermore, key challenges to be solved in order to create materials by design, reproducible process technology and society-centered solutions specifically for the two abovementioned technology sectors are analyzed. Overall, advances in aerogel technology can yield innovative and integrated solutions for environmental and life sciences which in turn can help improve both the welfare of population and to move towards cleaner and smarter supply chain solutions.